2020
DOI: 10.51377/azjaf.vol1no01.7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Of Zakat Funds To Achieve SDGs Through Poverty Alleviation In Baznas Republic Of Indonesia

Abstract: Exterminating poverty and inequality is a present challenge that the SDGs want to overcome. Sustainable Development Goals (SDGs) itself is a continuation of the previous platform of the Millennium Development Goals (MDGs), which was designed by the United Nations and agreed upon by 193 countries. SDGs applied with universal principles, integrity, and inclusive to ensure that all  arties can involve without exception, with the name No One Left Behind. The SDGs have 17 goals and 169 achievement targets,  hich ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 0 publications
1
12
0
2
Order By: Relevance
“…In contrast, investment, government spending and local revenue have a direct and insignificant effect on economic growth. It found that the immediate impact of private investment, government spending and labour on economic growth was greater than the indirect effect of private investment, government spending and work on economic growth through local revenue (Hasan, 2020a).…”
Section: Figure 1 Economic Growth In Riau Provincementioning
confidence: 98%
“…In contrast, investment, government spending and local revenue have a direct and insignificant effect on economic growth. It found that the immediate impact of private investment, government spending and labour on economic growth was greater than the indirect effect of private investment, government spending and work on economic growth through local revenue (Hasan, 2020a).…”
Section: Figure 1 Economic Growth In Riau Provincementioning
confidence: 98%
“…Communities residing in disaster-prone areas need to be educated about disaster mitigation, and governments should provide adequate infrastructure and resources for disaster mitigation [40]. Civil society organizations, Zakat management institutions, and humanitarian organizations can assist in disaster mitigation efforts [9]. Actions that can be taken in disaster mitigation include building disaster-resistant infrastructure, developing early warning systems, educating the community on disaster preparedness, and conducting disaster preparedness simulations and exercises [41].…”
Section: Zakat and Disaster Mitigationmentioning
confidence: 99%
“…One form of donation with great potential is Zakat. Zakat plays a significant role in strengthening efforts to reduce the impact of disasters because the funds can be used for various protection, prevention, and post-disaster recovery activities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Almost 80%-90% of Islamic banks operate based on the Mudarabah model, as it provides more freedom for firms to operate with having no interference from bank in the management decisions of the firm. According to Dhumale and Sapcanin (1998) and Hassan (2010), in this model, Islamic banks need to arrange the money for short-term purposes to fulfil their financial requirements for meeting the day-to-day basis operations.…”
Section: Working Capital Management Perspectives -Islamic Finance Con...mentioning
confidence: 99%